2013
DOI: 10.1088/0022-3727/46/43/435401
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of plasma-generated radicals in liquids by electron paramagnetic resonance spectroscopy

Abstract: This work focused on qualitative and quantitative detection of oxygen free radicals in liquids after plasma treatment with an atmospheric pressure argon plasma jet by electron paramagnetic resonance spectroscopy (EPR). For the treatment, a shielded plasma jet, where the active effluent zone is surrounded by a protective gas curtain was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(153 citation statements)
references
References 48 publications
5
146
2
Order By: Relevance
“…Plasma exposure times exceeding 60 s showed dose-dependent caspase 3 activation up to 80% (360 s). This is consistent with the findings of Barton et al, who showed that cytotoxicity increases in THP-1 monocytes after long plasma exposure [37]. Recently, Avisetti et al showed the connection of JNK and caspase 3 activation due to reactive oxygen species exposure, which may be responsible for the plasma-induced caspase 3 activation in the monocytes [20].…”
Section: Apoptosis Induction In Response To Plasma Treatmentsupporting
confidence: 89%
“…Plasma exposure times exceeding 60 s showed dose-dependent caspase 3 activation up to 80% (360 s). This is consistent with the findings of Barton et al, who showed that cytotoxicity increases in THP-1 monocytes after long plasma exposure [37]. Recently, Avisetti et al showed the connection of JNK and caspase 3 activation due to reactive oxygen species exposure, which may be responsible for the plasma-induced caspase 3 activation in the monocytes [20].…”
Section: Apoptosis Induction In Response To Plasma Treatmentsupporting
confidence: 89%
“…This can be an indication that other ROS may be present after plasma treatment. 46 However, the 100% rescue observed by the presence of catalase seems to indicate that H 2 O 2 is the sole ROS active under these treatment conditions [Figs. 4 and 8(a)].…”
Section: -mentioning
confidence: 99%
“…23 Due to the short half-life of the radicals, a chemical agent is necessary for detection. This so called spin trap was used to stabilize the radicals for sufficient time.…”
Section: F Electron Paramagnetic Resonance Spectroscopymentioning
confidence: 99%
“…More information about the detailed measurement procedure and the evaluation process can be found in a previous publication. 23 …”
Section: F Electron Paramagnetic Resonance Spectroscopymentioning
confidence: 99%